UJI INTEGRASI PASAR MODAL DAN CONTAGION EFFECT SEBELUM DAN SESUDAH BREXIT PADA PASAR MODAL ASEAN - Prayogo Prayogo; Harijono Harijono; Robiyanto Robiyanto (Faculty of Economics and Business Udayana University, 2019)
This study examined capital market integration and contagion effect among ASEAN and UK capital markets. Data analysis will be divided to before the Brexit (January 2012 – 22 June 2016) and after the Brexit (24 June 2016 – December 2016). The analytical tool used is Vector Autoregressive (VAR) to analyze the integration between capital markets and Granger Causality to detect any contagion effect between capital markets. The conclusion of this research is existance of Brexit event can change the segmented ASEAN-5 region become more integrated. It’s found that the Singapore capital market is a capital market that recieves a contagion effect from the UK capital market before and after Brexit. As for the Indonesia, Malaysia, Philippines and Thailand’s capital markets only received contagion effects between regions, except Philippines capital market after Brexit does’t accept contagion effect from all countries.